PROJECT ACTIVITY OF STUDENTS IN PHYSICS LESSONS - ONE OF THE DIRECTIONS OF DEVELOPMENT OF MODERN EDUCATION (Pedagogy of Higher and Secondary Education, 2010)
The question of introduction of innovative technologies of studies is examined in the article - important factor of organization and development of society. One of types of innovative technologies there is a method of projects, which allows to decide the various tasks of creative development of students.
Keywords: innovative technologies; method of projects; creative development creative activity